Uji Marshall Terhadap Material Lokal Berporositas Tinggi - yasara rizli; Sofyan M. Saleh; Yusria Darma (Journal of The Civil Engineering Student, 2020)
AbstractConstruction of a highway in Indonesia for a road with heavy traffic load is a layer of Asphalt Concrete - Wearing Course. Utilization of local materials is expected to be used optimally to improve efficiency in terms of financing, especially in particular areas such as islands, Sabang, Aceh province. This research aims to determine the effect of the use of Sabang fine aggregates with high porosity values of 4.08% on concrete asphalt mixtures. The initial phase of this research is to find the optimum bitumen content (OBC). Then the manufacture of the test specimen was done with a combination of Sabang fine aggregate. From the results of the research, the composition used to maximize the use of local material is 50% of Sabang fine aggregate and 50% of Aceh Besar fine aggregate at 5.87% asphalt content. The result of the research shows the value of stability is 1225.81 kg and value flow is 3.23 mm. research on the stability of the Value declined by 15.10%, while the value of the flow declined by 1.12% of the standard mixture.Keywords : Asphalt Concrete, Fine Aggregates with High, Sabang Fine Aggregates, Portland Cement FillerAbstrakKonstruksi jalan raya di Indonesia untuk jalan dengan beban lalu lintas berat merupakan lapisan aspal beton (LASTON). Pemanfaatan material lokal diharapkan dapat digunakan secara maksimal untuk meningkatkan efisiensi dari sisi pembiayaan, khususnya daerah kepulauan seperti Kota Sabang, Provinsi Aceh. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan agregat halus Sabang dengan nilai porositas tinggi yaitu 4,08% pada campuran aspal beton. Tahap awal penelitian ini adalah mencari nilai kadar aspal optimum (KAO). Selanjutnya dibuat benda uji dengan beberapa kombinasi agregat halus Sabang. Dari hasil penelitian komposisi yang digunakan untuk memaksimalkan penggunaan material lokal adalah 50% agregat halus Sabang dan 50% agregat halus Aceh Besar pada kadar aspal 5,87%. Hasil dari penelitian menunjukkan nilai stabilitas adalah 1225,81 kg dan nilai flow adalah 3,23 mm. Nilai stabilitas pada penelitian ini menurun sebesar 15,10%, sedangkan nilai flow menurun sebesar 1,12% dari campuran standar.Kata kunci: Aspal beton, Agregat Porositas Tinggi, Agregat Halus Sabang, Filler Portland Cement